Students empowerment in campus sustainability through art installation project - Shahida Mohd Sharif; Izyan Ayuni Mohamad Selamat; Januarius Gobilik (Universiti Malaysia Sabah, 2017)
Campus sustainability is a movement that requires a significant engagement from various campus stakeholders. Students as the biggest stakeholders have to play a meaningful role as the implementers, and academicians, on another side, must feel free to address campus sustainability issues and inspire the students to get involved in making the campus sustainability movement a reality. In 2013, Universiti Malaysia Sabah established an EcoCampus Management Centre to lead the sustainability movement to a higher level. The goal of the university is becoming an EcoCampus by 2018. Thus, in parallel with the goal of the movement, the Horticulture and Landscaping Programme (HG35), Faculty of Sustainable Agriculture (FSA), UMS has set out one of the Programme learning outcomes as to produce graduates who could grasp the concepts and principles of sustainable horticulture and landscaping. Several HG35 academicians and Key Persons appointed by the UMS authority had implemented the EcoCampus Core Values and Key Elements in teaching and learning activities. In this paper, the authors share their experience in integrating the sustainability movement in teaching and learning process for Garden Planning and Management course. A project-based learning (PBL) named EcoProject was structured to empower the students of the course to create something that could achieve the goal of the sustainability movement and most importantly is meaningful to them. The assessment is designed to allow the students (1) to integrate a variety of knowledge and skills pertaining to horticulture and landscaping in their projects, 2) to give a platform to the students to explore and adopt a sustainable initiative in FSA campus creatively, and 3) to foster a sense of belonging to the sustainability movement introduced by the University. The performance of the students was then evaluated using a Likert scale. At the end of the project, the students produced several distinctive art installations, for example, a lath house, that is, a shelter made of 1000 recycled 1.5L transparent plastic water bottles functioning as a plant nursery especially for acclimatising young seedlings before field planting. The EcoProject assessment had demonstrated that sustainability movement could be harmoniously integrated into teaching and learning activities in higher education institutions. The project had inspired the students to be creative and confident to engage in a sustainability movement, and this experience is expected to stay with them once graduated.